Venetoclax combined with FLAG‐IDA induction and consolidation in newly diagnosed acute myeloid leukemia. Issue 8 (30th May 2022) - DiNardo, Courtney D.; Lachowiez, Curtis A.; Takahashi, Koichi; Loghavi, Sanam; Kadia, Tapan; Daver, Naval; Xiao, Lianchun; Adeoti, Maria; Short, Nicholas J.; Sasaki, Koji; Wang, Sa A.; Borthakur, Gautam; et al.
Abstract: Multi‐agent induction chemotherapy (IC) improves response rates in younger patients with acute myeloid leukemia (AML); however, relapse remains the principal cause of treatment failure. Improved induction regimens are needed. A prospective single‐center phase Ib/II study evaluating fludarabine, cytarabine, G‐CSF, and idarubicin combined with venetoclax (FLAG‐IDA + VEN) in patients with newly diagnosed (ND) or relapsed/refractory AML. The primary efficacy endpoint was assessment of overall activity (overall response rate [ORR]: complete remission [CR] + CR with partial hematologic recovery [CRh] + CR with incomplete hematologic recovery [CRi] + morphologic leukemia free state + partial response). Secondary objectives included additional assessments of efficacy, overall survival (OS), and event‐free survival (EFS). Results of the expanded ND cohort with additional follow‐up are reported. Forty‐five patients (median age: 44 years [range 20–65]) enrolled. ORR was 98% ( N  = 44/45; 95% credible interval 89.9%–99.7%). Eighty‐nine percent ( N  = 40/45) of patients attained a composite CR (CRc + CRh + CRi) including 93% ( N  = 37/40) who were measurable residual disease (MRD) negative. Twenty‐seven (60%) patients transitioned to allogeneic stem cell transplant (alloHSCT). Common non‐hematologic adverse events included febrile neutropenia (44%; N  = 20), pneumonia (22%, N  = 10), bacteremia (18%, N  = 8), and skin/soft tissue infections (44%, N  = 20). After a median follow‐up of 20 months, median EFS and OS were not reached. Estimated 24‐month EFS and OS were 64% and 76%, respectively. FLAG‐IDA + VEN is an active regimen in ND‐AML capable of producing high MRD‐negative remission rates and enabling transition to alloHSCT when appropriate in most patients. Toxicities were as expected with IC and were manageable. Estimated 24‐month survival appears favorable compared to historical IC benchmarks.